Analisis Peningkatan Kompetensi Guru di MGMP Al-Qur’an Hadis Madrasah Aliyah Kabupaten Demak - Zarkasi Zarkasi; M. Afief Mundzir; Abdul Rokhim; Parsidi Parsidi; Julhadi Julhadi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to analyze the learning practices that have been carried out by Al-Qur'an Hadith teachers at Madrasah Aliyah in Demak Regency, Central Java Province who are members of the MGMP. This research is qualitative with a phenomenological approach. Data was collected using observation, documentation, and interviews. Next, the data was analyzed using several steps: collection, reduction, data presentation, and conclusion. The results of the research show that the majority of learning practices carried out by al-Qur'an hadith teachers at Madrasah Aliyah in Demak Regency are still classical, dominated by lectures, the media and learning methods used are less varied and adaptive, the learning is still focused on the teacher (not yet focused on students), have not made much use of technology or the internet and have not directed students' critical thinking skills. This research produces an analysis that to improve the quality of learning, the steps that must be taken are to increase innovation and knowledge through various online and offline training, take part in teacher professional education (PPG), and improve educational qualifications toward master's and doctoral levels so that the quality and competence of teachers increases as well as The learning is also more contextual and fun for students who are learning